Smartphone Repurchase Decisions Mediated by Customer Satisfaction - Prihantini, Prihantini; Manggabarani, Alfatih Sikki; Wikantari, Maria Assumpta (PT Mattawang Mediatama Solution, 2024)
This research analyzes smartphone repurchase decisions occurred in the Jabodetabek area. The aim of this research is to determine, analyze, and prove whether lifestyle, brand preference, and brand awareness affects smartphone repurchases, as well as to examine the effect of lifestyle, brand preference, and brand awareness on smartphone repurchases mediated by customer satisfaction. This research used quantitative method by distributing questionnaires to 215 smartphone user customers in the Jabodetabek area using the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) alternative with the Smart-PLS 4.0 program. The results of data analysis indicate that: Lifestyle and brand awareness have a significant influence on the decision to repurchase a smartphone, and brand preference does not have a significant influence on the decision to repurchase a smartphone. The research also found that lifestyle, brand preference, and brand awareness have a significant influence on smartphone repurchase decisions mediated by customer satisfaction.